Epworth League Institute Conference at Dardanelle - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
The members of the Epworth League Institute gather together for a group photograph to commemorate the conference at Dardanelle, California. Smaller groups within the main group identify themselves by displaying signs indicating where they are from and also by wearing similar, identifying clothing or hats.